Between the interstices of democracy: student magazines, the uruguayan university in transition and contestations over the meaning of democracy - González Vaillant, Gabriela (Revista de Historia Social y de las Mentalidades, 2024)
This paper analyzes the process of reorganization of the Uruguayan university student movement in the early years of the eighties and specifically during the period between 1980 and 1983. The work seeks to trace the genesis of the reconstitution of this social and political actor to through a careful analysis of the student magazines that emerged during this period, proposing an alternative look at democratic transitions beyond the political partisan spheres. The work concludes that the student magazines constituted alternative channels of expression, but also privileged spaces to forge and catalyze a generational and student identity and sensitivity during a period in which traditional channels of participation and activism were unavailable.
Keywords: Students; University; Magazines; Alternative Media; Uruguay